What is the evidence on availability and integration of refugee and migrant health data in health information systems in the WHO European Region?: Themed issues on migration and health, X - Bozorgmehr, Kayvan; Biddle, Louise; Rohleder, Sven; Jahn, Rosa (World Health Organization, 2019)
The recent rapid increases in population movements across borders highlight the importance of reliable data on refugee and migrant health for public health planning. This scoping report examined evidence on the availability and integration of refugee and migrant health data in health information systems in the WHO European Region
Gesehen am 03.02.2020